Therapeutic Renin Inhibition in Diabetic Nephropathy—A Review of the Physiological Evidence - Massolini, Bianca Domingues; Contieri, Stephanie San Gregorio; Lazarini, Giulia Severini; Bellacosa, Paula Antoun; Dobre, Mirela; Petroianu, Georg; Brateanu, Andrei; Campos, Luciana Aparecida; Baltatu, Ovidiu Constantin (Frontiers in Physiology, 2020)
The purpose of this systematic review was to investigate the scientific evidence to support the use of direct renin inhibitors (DRIs) in diabetic nephropathy (DN). MEDLINE was searched for articles reported until 2018. A standardized dataset was extracted from articles describing the effects of DRIs on plasma renin activity (PRA) in DN. A total of 3 clinical articles studying PRA as an outcome measure for DRIs use in DN were identified. These clinical studies were randomized controlled trials (RCTs): 1 double-blind crossover, 1 post hoc of a double-blind and placebo-controlled study, and 1 open-label and parallel-controlled study. Two studies reported a significant decrease of albuminuria associated with PRA reduction. One study had a DRI as monotherapy compared to placebo, and 2 studies had DRI as add-in to an ARB. Of 10393 patients with DN enrolled in 5 studies with DRI, 370 (3.6%) patients had PRA measured. Only one preclinical study was identified determined PRA when investigating the effects of aliskiren in DN. Moreover, most of observational preclinical and clinical studies identified report on a low PRA or hyporeninemic hypoaldosteronism in DM. Renin inhibition has been suggested for DN, but proof of concept studies for this are scant. A small number of clinical and preclinical studies assessed the PRA effects of DRIs in DN. For a more successful translational research for DRIs, specific patient population responsive to the treatment should be identified and PRA may remain a biomarker of choice for patient stratification.